The role of LncRNAs and CircRNAs in osteoporosis: a focus on osteogenesis and osteoclastogenesis signaling pathways - Suzan M. Ismail; Mai A. Abd-Elmawla; Marwa I. Shabayek; Hebatallah A. Darwish; Maha M. El-Sawalhi (SpringerOpen, 2024)
Abstract Background Osteoporosis is a crucial health concern interconnected with physical disabilities as well as financial burdens. It arises from an imbalance between osteoblasts and osteoclasts, provoking the reduction of bone mass and the disturbances in bone structure with high fracture risk. Considerable efforts were done to prevent and mitigate this public health issue. Nonetheless, further understanding of the etiopathology of osteoporosis and the underlying genetic and epigenetic pathways is required. Main body Emerging evidence indicates that noncoding RNAs, including long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs), play crucial roles as epigenetic regulators in various pathological processes, including osteoporosis. LncRNAs are RNA transcripts with higher structural complexity that are developed owing to their secondary and tertiary structures, which allow them to create different binding sites for other biomolecules, such as DNA, RNA, and proteins. Another class of noncoding RNAs is circRNAs, which have a covalently closed loop structure without the 5' cap and 3' polyA tail and are formed by back-splicing of pre-mRNAs. Because of their closed structure, circRNAs are largely stable, resistant to RNA-degrading nucleases, and possess substantially longer circulatory half-lives than linear RNAs. Interestingly, both lncRNAs and circRNAs serve as competing endogenous RNAs by sponging multiple miRNA binding sites as well as interact with RNA-binding proteins (RBPs), thereby controlling the expression of their target genes. Several studies indicated that altered expression of these regulators could influence many biological processes in bone cells. Conclusion The current review provides current opinions on the role and the underlying mechanisms by which lncRNAs and circRNAs affect osteoblastic and osteoclastic activities. The deep understanding of these noncoding RNAs in osteoporosis offers distinctive avenues for innovative treatment strategies.